The Biology of Gastric Cancers - Wang, Timothy (Springer, 2017)
There have been many impressive advances in our understanding of the pathogenesis of gastric adenocarcinoma, gastric MALT lymphoma, gastrointestinal stromal tumors of the stomach, and gastric carcinoid tumors over the years. "The Biology of Gastric Cancers," edited by Dr. Timothy Wang, Dr. James Fox and Dr. Andy Giraud, pays homage to the cutting edge concepts of cancer stem cells, tumor microenvironment, chronic inflammation, and genetic susceptibility to cancer and represents the very first volume devoted to the subject of the basic biology of gastric cancer. With an emphasis on animal models, but also considerable attention to human studies, host genetics and the role of bacterial factors and other environmental factors influencing the pathogenesis of gastric cancer, the topics presented in this book should be of interest to clinicians and investigators interested in gastrointestinal cancer, as well as basic investigators in related areas of cancer research. This body of work will hopefully stimulate clinical and translational studies that will advance early diagnosis and treatment of gastric tumors.